Ecological thresholds and abrupt transitions of tallgrass prairie to shrublands and woodlands - Ratajczak, Zak (Kansas State University, 2014)
Ecological thresholds are breakpoints where small increases in external pressure can generate rapid and difficult to reverse ecological transitions. Often, ecological thresholds are not recognized until they are crossed at a large-scale, leading to unintended and lasting externalities. In tallgrass prairie, we identified ecological thresholds of 3-year fire returns and ~60% grass cover, based on mechanistic field studies and long-term fire and grazing experiments. When tallgrass prairie is pushed passed these thresholds, it makes an abrupt transition to a self-reinforcing shrubland state. Demographic bottlenecks, niche partitioning, and altered fire feedback mechanisms account for both the non-linear nature of grassland-shrubland transitions and the resistance of established shrublands to fire and drought. In the last decade, only ~27% of Central Great Plains tallgrass prairie was burned every 1-2 years, and therefore ~73% of this region is susceptible to shrubland and woodland transitions in the next two to three decades. If transitions to shrublands and woodlands do occur, we expect a multi-trophic loss of grassland biodiversity, decreased cattle production, and the potential for damaging woodland fires in close proximity to human development. However, knowledge of fire thresholds, adaptive management tools, and bottom-up citizen action campaigns are creating a rare window of opportunity to avoid transformation of the remaining tallgrass prairies.
Keywords: Resilience; Ecology (0329)